VOM FUROR ZUR ECSTASIS Augustins Ekstase-Konzeption (Gen. ad litt. 12) im Kontext antiker / spätantiker Divination - Vultaggio, Cristina (Jahrbuch für Antike und Christentum, 2018)
In Gen. ad litt. 12 Augustine discusses a model of ecstatic divination, which he calls ecstasis/extasis. It is characterized by visions instead of given words or verses received in a state of frenzy. This article focuses on Augustine's reception of earlier pagan and Christian authors who dealt with this topic, and on the contextualization in Augustine's contemporary world.